Asparagine Synthetases of Klebsiella aerogenes: Properties and Regulation of Synthesis - Reitzer, Lawrence J. (1982)
We isolated pleiotropic mutants of Klebsiella aerogenes with the transposon Tn5 which were unable to utilize a variety of poor sources of nitrogen. The mutation responsible was shown to be in the asnB gene, one of two genes coding for an asparagine synthetase. Mutations in both asnA and asnB were necessary to produce an asparagine requirement. Assays which could distinguish the two asparagine synthetase activities were developed in strains missing a high-affinity asparaginase. The asnA and asnB genes coded for ammonia-dependent and glutamine-dependent asparagine synthetases, respectively. Asparagine repressed both enzymes. When growth was nitrogen limited, the level of the ammonia-dependent enzyme was low and that of the glutamine-dependent enzyme was high. The reverse was true in a nitrogen-rich (ammonia-containing) medium. Furthermore, mutations in the glnG protein, a regulatory component of the nitrogen assimilatory system, increased the level of the ammonia-dependent enzyme. The glutamine-dependent asparagine synthetase was purified to 95%. It was a tetramer with four equal 57,000-dalton subunits and catalyzed the stoichiometric generation of asparagine, AMP, and inorganic pyrophosphate from aspartate, ATP, and glutamine. High levels of ammonium chloride (50 mM) could replace glutamine. The purified enzyme exhibited a substrate-independent glutaminase activity which was probably an artifact of purification. The tetramer could be dissociated; the monomer possessed the high ammonia-dependent activity and the glutaminase activity, but not the glutamine-dependent activity. In contrast, the purified ammonia-dependent asparagine synthetase, about 40% pure, had a molecular weight of 80,000 and is probably a dimer of identical subunits. Asparagine inhibited both enzymes. Kinetic constants and the effect of pH, substrate, and product analogs were determined. The regulation and biochemistry of the asparagine synthetases prove the hypothesis strongly suggested by the genetic and physiological evidence that a glutamine-dependent enzyme is essential for asparagine synthesis when the nitrogen source is growth rate limiting.